Improving accessibility through referral management: setting targets for specialist care. Issue 2 (1st July 2017) - Greenwood-Lee, James; Wild, Geoff; Marshall, Deborah
Abstract: The use of optimized referral distribution strategies to improve access to specialty care is assessed. A mathematical model of a generalized care pathway is developed and the distribution of referrals is posed as an optimization problem. The objective is to minimize time from referral to a targeted stage in the care pathway (e.g., specialist consult, surgery, etc.). Numerical simulations informed by data on hip and knee surgeries demonstrate wait reductions from 21 to 38 days (16.8–30.4%) from time of referral to time of consult and from 33 to 66 days (12.6–24.7%) to time of surgery. However, the optimized referral distribution strategy minimizes wait times to the targeted stage only; wait times to non-targeted stages in the care pathway are suboptimal and may increase as an unintended consequence. Consequently, to achieve desired improvements in access, the targeted stage for wait time minimization must be carefully identified and prioritized.